SIKAP KELUARGA TERHADAP KEHADIRAN AUTISME: SALAH SATU BENTUK KOMUNIKASI KELUARGA - Yopi Kusmiati (Wardah, 2018)
Abstract: Having a family member of an autistic child is often a problem for a family, because not all family members can immediately accept the condition of the autistic child. Some think that autistic children become barriers to freedom in the family to act and carry out activities, because they must focus on serving and caring for children with autism. There are those who consider it a family disgrace, and a severe ordeal for all family members, so that the family experiences its own stressor, worried about the child's future. In fact, family acceptance to autistic children can support the development of the health of autistic children, especially their ability to interact with the environment, as seen from their attitudes towards children with autism. So in this study the author will look at how family attitudes toward the presence of autism children. This research was conducted with qualitative methods with a subjective approach and using phenomenological theory, to explore the experience of informants in depth. The results of the study found three family attitudes when they found out their children were autism, namely: (1) receiving, (2) accepting with rejection, (3) refusing. Keyword: Family attitudes, autism, family communication